The structure–function relationship of thrombin-like enzymes from the green pit viper (Trimeresurus albolabris). (15th June 2015) - Pradniwat, Paweena; Rojnuckarin, Ponlapat
Abstract: Pit viper venoms can decrease fibrinogen levels in snakebite patients. Studies have shown that the hypofibrinogenemia is a consequence of snake venom thrombin-like enzymes (TLEs), the serine proteases that have the potential to be both diagnostic and therapeutic agents. Exosites of thrombin are the molecular regions that determine the substrate specificities, but its presence and significance in TLEs are unclear. Therefore, the putative exosites of recombinant TLEs derived from Green pit viper ( Trimeresurus albolabris ), GPV-TL1 and GPV-TL2, were mutated in a Pichia pastoris system. In a previous report, GPV-TL1 showed a strong fibrinogenolytic activity on the Aα and Bβ chains of fibrinogen, as well as a plasma clotting activity. Compared with GPV-TL1, the GPV-TL1m mutated in the putative exosite (TRN to RRR at residues 60–62) showed a weaker fibrinogenolytic activity with a similar clotting activity of 207.1 thrombin units/mg. GPV-TL2 contained two-residue differences from GPV-TL1 in the putative exosite (N73M and V74Y). GPV-TL2 selectively cleaved only the Aα chain of fibrinogen without detectable clotting activity. The mutated GPV-TL2 (GPV-TL2m) showed a weaker fibrinogenolytic activity compared with that of the wild type. These results support the important roles of the putative exosite in snake venom TLE activities. This information is helpful for future protein engineering. Highlights: We expressed and characterized recombinant thrombin-like enzymes (TLEs) from Green pit viper (GPV). Recombinant GPV-TL2 with a different exosite showed lower activities compared with GPV-TL1. Recombinant GPV-TLs with mutated exosites showed lower fibrinogenolytic activities. The putative exosite in snake venom TLE is important for its enzymatic activities.